Melanin Synthesis Pathway Interruption: CRISPR/Cas9-mediated Knockout of dopa decarboxylase (DDC) in Harmonia axyridis (Coleoptera: Coccinellidae). Issue 5 (9th September 2022) - Wu, Meng-meng; Chen, Xu; Xu, Qing-xuan; Zang, Lian-sheng; Wang, Su; Li, Ming; Xiao, Da
Abstract: CRISPR/Cas9 technology is a very powerful genome editing tool and has been used in many insect species for functional genomics studies through targeted gene mutagenesis. Here, we successfully established CRISPR/Cas9 research platform in Asian multi-colored ladybird beetle, Harmonia axyridis, an important natural enemy in biological control. In this study, one pivotal gene dopa decarboxylase ( DDC ) in melanin synthesis was targeted by CRISPR/Cas9 to generate mutants in H. axyridis by CRISPR/Cas9 technology. Our results showed that injection of single guide RNA of the DDC and Cas9 protein into preblastoderm eggs induced one insertion and four deletion (indels) mutant H. axyridis . Mutations of HaDDC gene generated 25% mutant rate with melanin missing phenotype in larva, pupa, l and adult stage. The predation ability of the fourth instar larvae has no significant difference between wild (control) and mutant H. axyridis (G0), while these mutant fourth instar larvae had longer developmental period than that of the wild type. Consequently, the total predation of the fourth instar larvae was significantly increased in H. axyridis mutants comparing with the wild type. These results indicated that the success of CRISPR/Cas9 gene editing in H. axyridis . The gene editing platform in H. axyridis would facilitate the gene function research and promote special strain of predatory ladybird beetle generation.